Distribution of common zooplankton in razor clam (solen sp.) area at Kuching Bay, Sarawak - Jane Francesca, G. Volin, (Universiti Malaysia Sarawak (UNIMAS), 2005)
A study on the distribution of common zooplankton in razor calm (Solen sp.) area was carried out at all tide zones in the Kuching Bay of Sarawak. The primary aim of this study was to find out the distribution of common zooplankton and its relation to the physico-chemical of the water. As results, 79 species and about 58 families were identified. These species group were commonly found highly distributed at all the study area included: Oithona spp., Pseudocalanus spp., Paracalanus spp., Thespesiopsyllus spp., nauphli copepods and Cerviniopsis spp. However, Oithona spp. was the most abudance genera graoup found highly distributed with higher percentage values.